2005
DOI: 10.1063/1.2084715
|View full text |Cite
|
Sign up to set email alerts
|

Using the System Schema Representational Tool to Promote Student Understanding of Newton’s Third Law

Abstract: The Modeling Instruction program at Arizona State University has developed a representational tool, called a system schema, to help students make a first level of abstraction of an actual physical situation [1]. A system schema consists of identifying and labeling all objects of interest from a given physical situation, as well as all the different types of interactions between the objects. Given all the relevant objects and their interactions, students can explicitly identify which are part of their system an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 8 publications
0
22
0
2
Order By: Relevance
“…The tasks are posed with a single representational format, for example, a task with a graphical format only or another one presented solely in symbolic form. In contrast, for studies concerned with multiple representations, a given task is often structured with different kinds of representations presented either sequentially [30,[32][33][34] or in parallel [31,36]. In our study, the strategies employed across the different tasks posed with a single representational format were considered together and used to infer the kinds of mental representations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tasks are posed with a single representational format, for example, a task with a graphical format only or another one presented solely in symbolic form. In contrast, for studies concerned with multiple representations, a given task is often structured with different kinds of representations presented either sequentially [30,[32][33][34] or in parallel [31,36]. In our study, the strategies employed across the different tasks posed with a single representational format were considered together and used to infer the kinds of mental representations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were also geared towards exploring problem solving performance and hence differences in strategies with a change in representation [26][27][28]. The application of multiple representations for conceptual understanding [29,30] and enhancing problem solving performance [31,32] was additionally explored. Moreover, studies have looked into the possible factors leading to the ineffectiveness of teaching and learning based on multiple representations [27,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the ability to present information in various representational modes, to interpret and unpack information from a given depiction, and to use this information to generate different representations are scientific skills which students need to develop [17]. Studies concerned with representational issues in problem solving have focused on investigating students' handling of graphical and diagrammatic representations [18][19][20], teaching the use of multiple representations, and exploring its effect on students' problem solving performance [21][22][23][24][25] and conceptual understanding [26][27][28][29]. Research studies have also explored students' performance with multiple representations compared to single depictions [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…These include some representations that we would expect to be favored by returning students, such as energy pie charts [12] and system schema [31], which were developed for and almost exclusively used in Modeling Instruction courses. However, there are also several representations including assumptions, graphs, and motion maps that we might expect to be universal (used by both lecture and Modeling Instruction course) that we see are favored by returning students.…”
Section: A Baseline-new Vs Returningmentioning
confidence: 99%
“…In comparison, research on students using multiple representations is much more sparse. Rosengrant, Etkina, and Van Heuvelen provide a summary of research on multiple representations in physics education research [4], which indicates that using multiple representations improves students conceptual understanding and ability to solve problems [31,32]. Traxler et al and De Leone and Gire have shown that students in reformed physics classes or inquiry-based classes use more representations than their lecture counterparts [9,33].…”
Section: Introductionmentioning
confidence: 99%